Isospin mass splittings from precision measurements of D*-D mass differences - BORTOLETTO, D. (Institutional Knowledge at Singapore Management University, 1992)
Using the decay modes, D*+→D+π0 and D*0→D0π0, we have measured the D*+−D+ and D*0−D0 mass differences to be 140±0.08±0.06 and 142.12±0.05±0.05 MeV, respectively. Combining these measurements with the Particle Data Group average for the D*+−D0 mass difference, we obtain isospin mass splittings for D*+−Dusp*0 and D+−D0 of 3.32±0.08±0.05 and 4.80±0.10 ±0.06 MeV. We discuss the implications of these measurements for models of isospin mass differences and model-dependent estimates of fD.